Inclusion Issues In Ecce: Teacher Leadership From A Critical Education Point Of View - I Made Ardika Yasa; Putu Kerti Nitiasih; Putu Nanci Riastini (Jurnal Syntax Transformation, 2023)
Early childhood education plays an important role in forming a solid foundation for child development. In this context, teacher leadership is a key factor in addressing inclusion issues in ECCE. This study aims to explore teacher leadership from the point of view of critical education in addressing the issue of inclusion in early childhood education units. The critical education approach emphasizes the development of critical and creative thinking skills in children, as well as their ability to ask questions and solve problems. Through literature review and conceptual analysis, this research reveals the close relationship between critical education and teacher leadership in early childhood education. The implications of critical education on teacher leadership can be seen in several aspects. First, critical education influences teachers' leadership mindsets and attitudes, encouraging them to become reflective, analytical, and innovative leaders and applying participatory leadership principles. Second, critical education influences the practice and learning strategies applied by teachers, by expanding discussion spaces, encouraging collaboration, and stimulating critical reflection in children. This research makes an important contribution to our understanding of the importance of critical education and teacher leadership in early childhood education. The implications of this research are expected to provide insights for curriculum development and learning strategies, as well as training and professional development for early childhood education teachers. In the face of complex future challenges, critical education-oriented early childhood education and strong teacher leadership will provide a solid foundation for holistic and sustainable child development to address inclusion issues.